Aspalathin alleviates skeletal muscle insulin resistance and mitochondrial dysfunction - Mazibuko-Mbeje, S. E; Mthembu, S. Xh; Muller, C. J. F; Ziqubu, K; Muvhulawa, N; Modibedi, R. V; Tiano, L; Dludla, P. V (Physiological research, 2022)
Natural compounds may bear promising therapeutic benefits against metabolic diseases such as type 2 diabetes mellitus (T2DM), which are characterized by a state of insulin resistance and mitochondrial dysfunction. Here, we examined the cellular mechanisms by which aspalathin, a dihydrochalcone C-glucoside unique to rooibos, may ameliorate palmitate-induced insulin resistance and mitochondrial dysfunction in cultured C2C12 myotubules. This current study demonstrated that aspalathin remains effective in improving glucose uptake in insulin-resistant skeletal muscle cells, supported by the upregulation of insulin-dependent signaling that involves the activation of insulin receptor (IR) and direct phosphorylation of protein kinase B (AKT). Interestingly, aspalathin also improved mitochondrial respiration and function, which was evident by an increased expression of carnitine palmitoyltransferase 1 (Cpt1), fatty acid transport protein 1 (Fatp1), sirtuin 1 (Sirt1), nuclear respiratory factor 1 (Nrf1), and transcription factor A, mitochondrial (Tfam). Importantly, our results showed that aspalathin treatment was effective in ameliorating the devastating outcomes of insulin resistance and mitochondrial dysfunction that are linked with an undesired pro-inflammatory response, by reducing the levels of well-known pro-inflammatory markers such as interleukin-6 (IL-6), tumor necrosis factor-alpha (TNF-alpha), and protein kinase C-theta (PKC-theta). Thus, beyond improving glucose uptake and insulin signaling, the current study brings a new perspective in the therapeutic benefits of aspalathin in improving mitochondrial respiration and blocking inflammation to attenuate the detrimental effect of palmitate in skeletal muscle cells.
Keywords: Muscle, Skeletal; kosterní svaly; Diabetes Mellitus, Type 2; mitochondrie; Humans; Palmitates; kosterní svalová vlákna; lidé; Muscle Fibers, Skeletal; Insulin; inzulin; glukosa; Glucose; diabetes mellitus 2. typu; palmitany; Insulin Resistance; Mitochondria; inzulinová rezistence